Bifurcation in the history of Uranus and Neptune: the role of giant impacts. Issue 4 (22nd November 2019) - Reinhardt, Christian; Chau, Alice; Stadel, Joachim; Helled, Ravit
ABSTRACT: Despite many similarities, there are significant observed differences between Uranus and Neptune: While Uranus is tilted and has a regular set of satellites, suggesting their accretion from a disc, Neptune's moons are irregular and are captured objects. In addition, Neptune seems to have an internal heat source, while Uranus is in equilibrium with solar insulation. Finally, structure models based on gravity data suggest that Uranus is more centrally condensed than Neptune. We perform a large suite of high-resolution SPH simulations to investigate whether these differences can be explained by giant impacts. For Uranus, we find that an oblique impact can tilt its spin axis and eject enough material to create a disc where the regular satellites are formed. Some of the discs are massive and extended enough, and consist of enough rocky material to explain the formation of Uranus' regular satellites. For Neptune, we investigate whether a head-on collision could mix the interior, and lead to an adiabatic temperature profile, which may explain its larger flux and higher moment of inertia value. We find that massive and dense projectiles can penetrate towards the centre and deposit mass and energy in the deep interior, leading to a less centrally concentrated interior for Neptune. We conclude that the dichotomy between the ice giants can be explained by violent impacts after their formation.